Composite enhanced polyester fiber for bags and suitcases and preparation method of composite enhanced polyester fiber
By combining modified nano zinc oxide and chitosan aqueous solution, antibacterial and moisture-absorbing polyester fibers were prepared, solving the problem of insufficient moisture absorption and antibacterial properties of polyester fibers in the luggage industry and achieving better application results.
Patent Information
- Application Number
- CN202511500283.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-21
- Publication Date
- 2025-11-18
AI Technical Summary
The application of polyester fiber in the luggage industry is limited by its dense molecular structure, poor moisture absorption, and lack of antibacterial ability.
Antibacterial and moisture-absorbing masterbatch is formed by combining modified nano zinc oxide, chitosan aqueous solution and polyethylene glycol, and then composite reinforced polyester fiber is prepared by melt spinning and heat setting treatment to improve its moisture absorption and antibacterial properties.
It improves the moisture absorption and antibacterial properties of polyester fibers, enhancing their application potential in the luggage industry.
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the field of polyester fibers, in particular to a composite reinforced polyester fiber for luggage and a preparation method thereof. BACKGROUND
[0002] Polyester, the scientific name of which is polyethylene terephthalate (PET) fiber, is the largest and most widely used synthetic fiber in the world today. It is derived from petrochemical products and is made by chemical synthesis. Polyester fiber has extremely excellent performance. Its greatest advantage is high strength and good elasticity, so polyester fabric is very wear-resistant, wrinkle-resistant, and has excellent shape retention. Clothing is durable and not easy to deform. It also has excellent light resistance and chemical corrosion resistance. In addition, polyester has poor moisture absorption, which makes it dry quickly and easy to dry after washing, but also leads to poor air permeability, easy static and dust absorption. Polyester has extremely wide applications, and can be used to make various clothing, home textile fabrics (such as curtains, sofa covers), industrial fabrics (such as ropes, tents, tire cords) and non-woven fabrics, etc. after pure spinning or blending with other fibers. Its comfort can also be improved through physical or chemical modification.
[0003] The patent with publication number CN112900076A discloses a multifunctional polyester fiber and a preparation method thereof, which comprises the following steps: S1: alkali treatment, the polyester fiber is ultrasonically immersed in the alkali solution for 2-3h, then taken out, washed and dried to obtain alkali-impregnated polyester fiber; S2: washing and drying, the impregnated polyester fiber is taken out, then washed with clean water and dried to obtain A; S3: preparation of auxiliary materials, 20-30 parts of nano graphene oxide are taken in sequence according to weight fraction. However, the prior art still has some deficiencies: the molecular structure of polyester fiber is tight, it has poor moisture absorption, and it does not have antibacterial ability itself, which limits its application in the field of luggage. SUMMARY
[0004] The present application aims to provide a composite reinforced polyester fiber for luggage and a preparation method thereof to solve the problems in the prior art.
[0005] In order to solve the above technical problems, the present application provides the following technical scheme: a composite reinforced polyester fiber for luggage, which is prepared from polyethylene terephthalate chips, polyethylene glycol, tris (2, 4-di-tert-butyl phenyl) phosphite, tetra [beta- (3, 5-di-tert-butyl-4-hydroxyphenyl) propionic acid] pentaerythritol ester, modified nano zinc oxide, tetrabutyl titanate, chitosan aqueous solution and acetic acid; the modified nano zinc oxide is prepared from gamma-aminopropyl triethoxysilane, an ethanol aqueous solution, acetic acid and nano zinc oxide.
[0006] Further, the degree of deacetylation of chitosan is 90-92%.
[0007] Further, the polyethylene terephthalate chip has an intrinsic viscosity of 0.65±0.01 dL / g.
[0008] Further, the polyethylene glycol has a molecular weight of 6000-8000.
[0009] Further, a preparation method of a composite reinforced polyester fiber for luggage includes the following steps: (1) polyethylene terephthalate chips are pre-dried in vacuum at 145-155°C for 1-2 hours; γ-aminopropyltriethoxysilane is mixed with an ethanol aqueous solution with a mass fraction of 50-60%, acetic acid is used to adjust the pH value to 5.5-6.0, stirring is performed at 50-60°C and a rotating speed of 200-300 rpm for 30-40 minutes, then nano zinc oxide with a particle size of 20-50 nm is added, ultrasonic treatment is performed at a power of 300-400 W for 30-40 minutes, filtration is performed, the product is washed with anhydrous ethanol for 2-4 times, then the product is placed in a vacuum drying box and dried in vacuum at 70-80°C for 4-6 hours to obtain modified nano zinc oxide; (2) half of the total mass of the dried polyethylene terephthalate chips, polyethylene glycol, tris(2,4-di-tert-butylphenyl) phosphite, tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid] pentaerythritol ester, the modified nano zinc oxide prepared in step (1), and tetrabutyl titanate are mixed, then the mixture is added into a twin-screw extruder and melt-extruded under nitrogen protection, the melt-extruded strip-shaped product is water-cooled and cut into particles to obtain antibacterial and moisture-absorbing master batches; (3) the antibacterial and moisture-absorbing master batches prepared in step (2) are mixed with the remaining dried polyethylene terephthalate chips, then melt spinning is performed to obtain a primary fiber bundle; (4) the primary fiber bundle is cooled and solidified under side-blowing conditions, the side-blowing speed is 0.4-0.6 m / s, and the blowing temperature is 19-21°C; the cooled primary fiber is pre-drafted through a godet, the pre-drawing ratio is 1.4-1.6 times, and then the primary fiber is main-drafted through a pair of hot rollers, the main-drawing ratio is 3.4-3.6 times, wherein the temperature of the hot rollers is set to 85-95°C to obtain polyester fibers; (5) the polyester fiber bundle is immersed in a chitosan aqueous solution with a mass fraction of 3-4%, one-immerse-one-roll is performed, the bath ratio is 1:10-20, the immersion time is 5-15 minutes, the immersion temperature is 40-60°C, the roll pressure is 0.3-0.5 MPa, and the wet pick-up rate is 70-80%, then the product is dried in an oven at 95-105°C for 4-6 minutes; (6) then the polyester fiber treated in step (5) is placed in a heat setting machine at 150-160°C in a relaxed state for heat setting treatment, the treatment time is 2-3 minutes, and the composite reinforced polyester fiber is obtained.
[0010] Further, the mass ratio of the nano-zinc oxide, the ethanol aqueous solution and the gamma-aminopropyl triethoxysilane in step (1) is 100:(400-420):(5-8).
[0011] Further, the temperature partition of the double screw extruder in step (2) is set as: the first zone 235-245℃, the second zone 245-255℃, the third zone 260-270℃, the fourth zone 260-270℃, the fifth zone 260-270℃, the die temperature is 255-265℃, the screw rotation speed is 190-210rpm, and the length-diameter ratio is 39-41:1.
[0012] Further, the mass ratio of the polyethylene terephthalate chip, the polyethylene glycol, the tris(2,4-di-tert-butylphenyl) phosphite, the tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid] pentaerythritol ester, the modified nano-zinc oxide and the tetrabutyl titanate in step (3) is (88-92):(8-12):(0.1-0.3):(0.1-0.3):(3-5):(0.1-0.5).
[0013] Further, the conditions of the melt spinning in step (3) are: the spinning plate aperture is 0.24-0.26mm, the spinning speed is 2900-3100m / min, and the spinning temperature is 265-275℃.
[0014] Further, the chitosan aqueous solution in step (5) is previously adjusted to pH 4.5-5.5 by acetic acid.
[0015] Compared with the prior art, the present application has the following beneficial effects: 1. This invention utilizes γ-aminopropyltriethoxysilane to surface-modify nano-zinc oxide. The ethoxy group of γ-aminopropyltriethoxysilane hydrolyzes to generate silanol groups, which undergo dehydration condensation with the zinc hydroxyl groups on the surface of the nano-zinc oxide to form strong Zn-O-Si covalent bonds. This introduces organically compatible groups and reactive amino groups into the nano-zinc oxide, inhibiting its agglomeration tendency and enhancing its compatibility and dispersion uniformity in the polymer matrix. Under high-temperature shearing, the terminal hydroxyl groups of polyethylene glycol undergo transesterification with the ester bonds or terminal carboxyl groups of polyethylene terephthalate (PET) to form a PET-PET block copolymer. The PET segments in the PET-PET block copolymer impart hygroscopicity to the fibers, while the uniformly dispersed nano-zinc oxide provides antibacterial properties. By treating the fibers with a chitosan aqueous solution, the amino groups of the chitosan molecules are protonated and transformed into positively charged ammonium ions under acidic conditions. These cationic groups combine with the negatively charged polyethylene terephthalate ester groups on the fiber surface through electrostatic interaction, constructing a natural polymer antibacterial layer on the fiber. By contacting and destroying the positively charged amino groups of microbial cell membranes, the antibacterial effect is enhanced together with zinc ions. Detailed Implementation
[0016] The following embodiments are provided to better understand the present invention and are not limited to the preferred embodiments described. They do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention.
[0017] A composite reinforced polyester fiber for bags is prepared from polyethylene terephthalate chips, polyethylene glycol, tris(2,4-di-tert-butylphenyl) phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], modified nano zinc oxide, tetrabutyl titanate, chitosan aqueous solution, and acetic acid; wherein the modified nano zinc oxide is prepared from γ-aminopropyltriethoxysilane, ethanol aqueous solution, acetic acid, and nano zinc oxide.
[0018] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products. Example
[0019] The polyethylene terephthalate chip is pre-dried in vacuum at 145℃ for 1 hour; the γ-aminopropyl triethoxysilane and 50% mass fraction ethanol aqueous solution are mixed, the pH value is adjusted to 5.5 with acetic acid, stirred at 50℃ and 200 rpm for 30 minutes, then the 20 nm nano zinc oxide is added, ultrasonic treatment is carried out for 30 minutes with 300 W power, filtration is carried out, washed twice with anhydrous ethanol, then placed in a vacuum drying oven, dried in vacuum at 70℃ for 4 hours to obtain the modified nano zinc oxide; wherein the mass ratio of nano zinc oxide, ethanol aqueous solution and γ-aminopropyl triethoxysilane is 100:400:5; Half of the total mass of the dried polyethylene terephthalate chip with intrinsic viscosity of 0.64 dL / g, polyethylene glycol with molecular weight of 6000, tris(2,4-di-tert-butylphenyl) phosphite, tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid] pentaerythritol ester, the modified nano zinc oxide prepared in step (1) and tetrabutyl titanate are mixed, then added into a twin-screw extruder for melt extrusion under nitrogen protection, the temperature partition of the twin-screw extruder is set as: 235℃ for the first zone, 245℃ for the second zone, 260℃ for the third zone, 260℃ for the fourth zone, 260℃ for the fifth zone, the temperature of the die head is 255℃, the screw rotation speed is 190 rpm, and the length-diameter ratio is 39:1; the melt strip extruded is water-cooled and cut into particles to obtain antibacterial and moisture-absorbing master batches; The antibacterial and moisture-absorbing master batches prepared in step (2) are mixed with the remaining dried polyethylene terephthalate chip, then melt spinning is carried out to obtain a primary fiber bundle, the spinning plate aperture is 0.24 mm, the spinning speed is 2900 m / min, and the spinning temperature is 265℃; the mass ratio of the polyethylene terephthalate chip, polyethylene glycol, tris(2,4-di-tert-butylphenyl) phosphite, tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid] pentaerythritol ester, modified nano zinc oxide and tetrabutyl titanate is 88:8:0.1:0.1:3:0.1; The primary fiber bundle is cooled and solidified under side-blowing condition, the side-blowing speed is 0.4 m / s, and the blowing temperature is 19℃; the cooled primary fiber is pre-drafted through a godet, the pre-drawing ratio is 1.4 times, and then main-drafted through a pair of hot rollers, the main-drawing ratio is 3.4 times, wherein the temperature of the hot roller is set as 85℃ to obtain polyester fibers; The polyester fiber bundle is immersed in a chitosan aqueous solution with a mass fraction of 3%, one-dip-one-roll is carried out, the bath ratio is 1:10, the immersion time is 5 minutes, the immersion temperature is 40℃, the roll pressure is 0.3 MPa, and the wet pick-up rate is 70%, then dried in an oven at 95℃ for 4 minutes; the degree of deacetylation of the chitosan is 90%, and the chitosan aqueous solution is pre-adjusted to a pH value of 4.5 with acetic acid; Then the polyester fiber treated by step (5) is placed in a heat setting machine at 150℃ in a relaxed state for heat setting treatment, and the treatment time is 2 minutes, to obtain the composite reinforced polyester fiber. Examples
[0020] The polyethylene terephthalate chips are pre-dried in vacuum at 150℃ for 1.5 hours; the γ-aminopropyl triethoxysilane and the 55% mass fraction ethanol aqueous solution are mixed, the pH value is adjusted to 5.8 with acetic acid, and stirred at 55℃ and 250rpm for 35 minutes, then the 35nm particle size nano zinc oxide is added, and ultrasonic treatment is performed at a power of 350W for 35 minutes, and then filtered and washed with anhydrous ethanol for 3 times, and then placed in a vacuum drying oven at 75℃ for 5 hours to obtain the modified nano zinc oxide; wherein the mass ratio of the nano zinc oxide, the ethanol aqueous solution and the γ-aminopropyl triethoxysilane is 100:410:6.5; Half of the total mass of the dried polyethylene terephthalate chips with an intrinsic viscosity of 0.65dL / g, polyethylene glycol with a molecular weight of 7000, tris(2,4-di-tert-butylphenyl) phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], the modified nano zinc oxide prepared in step (1) and tetrabutyl titanate are mixed and then added into a twin-screw extruder for melt extrusion under nitrogen protection, wherein the temperature partition of the twin-screw extruder is set as: 240℃ for the first zone, 250℃ for the second zone, 265℃ for the third zone, 265℃ for the fourth zone, 265℃ for the fifth zone, the die head temperature is 260℃, the screw rotation speed is 200rpm, and the length-diameter ratio is 40:1; the extruded melt strip is water-cooled and cut into particles to obtain antibacterial and moisture-absorbing master batches. The antibacterial and moisture-absorbing master batches prepared in step (2) are mixed with the remaining dried polyethylene terephthalate chips, and then melt spinning is performed to obtain a primary fiber bundle, wherein the spinneret aperture is 0.25mm, the spinning speed is 3000m / min, and the spinning temperature is 270℃; the mass ratio of the polyethylene terephthalate chips, the polyethylene glycol, tris(2,4-di-tert-butylphenyl) phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], the modified nano zinc oxide and tetrabutyl titanate is 90:10:0.2:0.2:4:0.3; The primary fiber bundle is cooled and solidified under side blowing condition, wherein the side blowing speed is 0.5m / s and the blowing temperature is 20℃; the cooled primary fiber is pre-drafted by a godet at a pre-drawing ratio of 1.5 times, and then main-drafted by a pair of hot rollers at a main-drawing ratio of 3.5 times, wherein the temperature of the hot rollers is set to 90℃ to obtain the polyester fiber. The polyester fiber tows are immersed in a 3.5% by mass aqueous chitosan solution, and are subjected to one dip and one roll, with a bath ratio of 1:15, a dipping time of 10 minutes, a dipping temperature of 50°C, a roll pressure of 0.4 MPa, and a wet pick-up of 75%, and are then dried in an oven at 100°C for 5 minutes; the degree of deacetylation of the chitosan is 91%, and the aqueous chitosan solution is previously adjusted to a pH of 5.0 with acetic acid; The polyester fiber treated in step (5) is then placed in a relaxed state in a heat setting machine at 155°C for heat setting treatment, with a treatment time of 2.5 minutes, to obtain the composite reinforced polyester fiber. Example
[0021] The polyethylene terephthalate chips are previously vacuum dried at 155°C for 2 hours; γ-aminopropyl triethoxysilane and a 60% by mass aqueous ethanol solution are mixed, the pH is adjusted to 6.0 with acetic acid, and stirring is carried out at 60°C and 300 rpm for 40 minutes, then 50 nm particle size nano zinc oxide is added, and ultrasonic treatment is carried out at a power of 400 W for 40 minutes, and the mixture is filtered and washed with anhydrous ethanol 4 times, and is then placed in a vacuum drying oven and vacuum dried at 80°C for 6 hours to obtain modified nano zinc oxide; the mass ratio of nano zinc oxide, aqueous ethanol solution and γ-aminopropyl triethoxysilane is 100:420:8; Half of the total mass of dried polyethylene terephthalate chips with an intrinsic viscosity of 0.66 dL / g, polyethylene glycol with a molecular weight of 8000, tris(2,4-di-tert-butylphenyl) phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], modified nano zinc oxide prepared in step (1) and tetrabutyl titanate are mixed and then added to a twin-screw extruder for melt extrusion under nitrogen protection, the temperature zones of the twin-screw extruder are set as follows: zone 1 245°C, zone 2 255°C, zone 3 270°C, zone 4 270°C, zone 5 270°C, the die head temperature is 265°C, the screw rotation speed is 210 rpm, and the length-diameter ratio is 41:1; the extruded melt strip is water-cooled and cut into particles to obtain antibacterial and moisture-absorbing master batches. The antibacterial and moisture-absorbing master batches prepared in step (2) are mixed with the remaining dried polyethylene terephthalate chips, and then melt spinning is carried out to obtain as-spun fiber tows, with a spinneret aperture of 0.26 mm, a spinning speed of 3100 m / min and a spinning temperature of 275°C; the mass ratio of polyethylene terephthalate chips, polyethylene glycol, tris(2,4-di-tert-butylphenyl) phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate], modified nano zinc oxide and tetrabutyl titanate is 92:12:0.3:0.3:5:0.5; The as-spun fiber bundle is cooled and solidified under side-blowing condition, the side-blowing wind speed is 0.6 m / s, and the blowing temperature is 21℃; the cooled as-spun fiber is first pre-drafted by a godet, the pre-drafting ratio is 1.6 times, and then main-drafted by a pair of hot rollers, the main-drafting ratio is 3.6 times, wherein the temperature of the hot roller is set to 95℃, to obtain the polyester fiber; The polyester fiber bundle is immersed in a chitosan aqueous solution with a mass fraction of 4%, one dip and one roll, the bath ratio is 1:20, the immersion time is 15 minutes, the immersion temperature is 60℃, the roll pressure is 0.5 MPa, and the wet pick-up rate is 80%, and then dried in an oven at 105℃ for 6 minutes; the degree of deacetylation of the chitosan is 92%, and the chitosan aqueous solution is previously adjusted to a pH value of 5.5 by acetic acid; Then the polyester fiber treated in step (5) is placed in a hot setting machine at 160℃ in a relaxed state for heat setting treatment, and the treatment time is 3 minutes, to obtain the composite reinforced polyester fiber.
[0022] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is only that the nano zinc oxide is not subjected to surface modification treatment by γ-aminopropyl triethoxysilane, but directly used without modification.
[0023] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is only that polyethylene glycol is not added.
[0024] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is only that the immersion process is not performed.
[0025] The breaking strength test is tested according to GB / T14344-2022. The moisture absorption performance is tested according to GB / T6503-2017. The fiber is woven into plain weave, the fabric density is 200 threads / cm, and then the antibacterial property is tested according to GB / T20944.3-2008. The performance analysis results of the examples and the comparative examples of the application are given in Table 1 below.
[0026] Table 1 Sample Breaking strength (cN / dtex) Moisture regain (%) Antibacterial rate (S. aureus) (%) Antibacterial rate (E. coli) (%) Example 1 4.7 1.4 99.5 99.2 Example 2 4.9 1.5 99.8 99.6 Example 3 4.6 1.6 99.2 98.9 Comparative Example 1 4.0 1.1 75.3 71.5 Comparative Example 2 5.0 0.6 98.2 97.5 Comparative Example 3 4.6 1.2 85.8 82.3 From the experimental data of the examples and comparative examples, it can be found that the present application uses γ-aminopropyl triethoxysilane modified nano zinc oxide as an antibacterial agent, polyethylene glycol as a moisture absorption modifier and a compatibilizer, and chitosan as a surface antibacterial finishing agent; wherein the γ-aminopropyl triethoxysilane forms a Zn-O-Si covalent bond through dehydration condensation of the silicon hydroxyl groups generated by its hydrolysis and the zinc hydroxyl groups on the surface of the nano zinc oxide, thereby introducing an organic aminopropyl segment on the surface of the nano zinc oxide, improving the dispersibility and interfacial compatibility of the nano zinc oxide in the polyethylene terephthalate matrix, and providing antibacterial properties through zinc ions; the polyethylene glycol undergoes an ester exchange reaction with the ester bonds or terminal carboxyl groups of the polyethylene terephthalate during the melt blending process, forming a polyethylene terephthalate-polyethylene glycol block copolymer, which destroys the regularity of the polyethylene terephthalate molecular chain and introduces hydrophilic segments, thereby creating diffusion channels and adsorption sites for water molecules and improving the moisture absorption of the fiber; the chitosan is protonated to form positively charged ammonium ions under acidic conditions, which are adsorbed on the negatively charged fiber surface through electrostatic interaction, and are further fixed through hydrogen bonds formed during the drying process, thereby constructing a natural polymer antibacterial layer on the fiber, and improving the antibacterial effect through the antibacterial action of the nano zinc oxide and the contact killing mechanism.
[0027] It will be apparent to those skilled in the art that the present application is not limited to the details of the above-exemplified embodiments but can be implemented in other concrete forms without departing from the spirit or essential characteristics of the present application. Therefore, the embodiments should be considered in all respects as illustrative and not restrictive, the scope of the present application being defined by the appended claims rather than the above description, and it is intended to embrace all changes and modifications that fall within the meaning and scope of equivalents of the claims. Any reference signs in the claims should not be construed as limiting the claims to which they belong.
Claims
1. A composite reinforced polyester fiber for bags, characterized in that, The composite reinforced polyester fiber is prepared from polyethylene terephthalate chips, polyethylene glycol, tris(2,4-di-tert-butylphenyl) phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], modified nano zinc oxide, tetrabutyl titanate, chitosan aqueous solution, and acetic acid; the modified nano zinc oxide is prepared from γ-aminopropyltriethoxysilane, ethanol aqueous solution, acetic acid, and nano zinc oxide.
2. The composite reinforced polyester fiber for bags according to claim 1, characterized in that... The degree of deacetylation of chitosan is 90-92%.
3. The composite reinforced polyester fiber for bags according to claim 2, characterized in that... The intrinsic viscosity of polyethylene terephthalate chips is 0.65 ± 0.01 dL / g.
4. The composite reinforced polyester fiber for bags according to claim 3, characterized in that... The molecular weight of polyethylene glycol is 6000-8000.
5. The method for preparing a composite reinforced polyester fiber for bags according to claim 4, characterized in that, Includes the following steps: (1) Pre-dry the polyethylene terephthalate slices under vacuum at 145-155℃ for 1-2 hours; γ-aminopropyltriethoxysilane and a 50-60% (w / w) aqueous ethanol solution were mixed, and the pH was adjusted to 5.5-6.0 with acetic acid. The mixture was stirred at 50-60°C and 200-300 rpm for 30-40 minutes. Then, nano-zinc oxide with a particle size of 20-50 nm was added, and the mixture was ultrasonically treated at 300-400 W for 30-40 minutes. The mixture was then filtered, washed 2-4 times with anhydrous ethanol, and then placed in a vacuum drying oven and vacuum dried at 70-80°C for 4-6 hours to obtain modified nano-zinc oxide. (2) Half of the total mass of dried polyethylene terephthalate chips, polyethylene glycol, tris(2,4-di-tert-butylphenyl) phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], modified nano zinc oxide obtained in step (1) and tetrabutyl titanate are mixed and added to a twin-screw extruder for melt extrusion under nitrogen protection. The extruded molten strips are then water-cooled and pelletized to obtain antibacterial moisture-absorbing masterbatch. (3) The antibacterial moisture-absorbing masterbatch obtained in step (2) is mixed with the remaining dried polyethylene terephthalate chips, and then melt-spun to obtain nascent fiber bundles. (4) The nascent fiber bundles are cooled and solidified under side blowing conditions. The side blowing speed is 0.4-0.6 m / s and the blowing temperature is 19-21℃. After cooling, the nascent fibers are first pre-stretched by guide rollers with a pre-stretch ratio of 1.4-1.6 times, and then main-stretched by a pair of hot rollers with a main stretch ratio of 3.4-3.6 times. The temperature of the hot rollers is set to 85-95℃ to obtain polyester fibers. (5) The polyester fiber bundle is immersed in a chitosan aqueous solution with a mass fraction of 3-4%, and then immersed and rolled. The bath ratio is 1:10-20, the immersion time is 5-15 minutes, the immersion temperature is 40-60℃, the rolling pressure is 0.3-0.5MPa, the liquid retention rate is 70-80%, and then dried in an oven at 95-105℃ for 4-6 minutes. (6) Then, the polyester fiber treated in step (5) is placed in a heat setting machine at 150-160℃ in a relaxed state for heat setting treatment for 2-3 minutes to obtain the composite reinforced polyester fiber.
6. The method for preparing a composite reinforced polyester fiber for bags according to claim 5, characterized in that... In step (1), the mass ratio of nano zinc oxide, aqueous ethanol solution and γ-aminopropyltriethoxysilane is 100:(400-420):(5-8).
7. The method for preparing a composite reinforced polyester fiber for bags according to claim 5, characterized in that... The temperature zones of the twin-screw extruder in step (2) are set as follows: Zone 1 235-245℃, Zone 2 245-255℃, Zone 3 260-270℃, Zone 4 260-270℃, Zone 5 260-270℃, the die head temperature is 255-265℃, the screw speed is 190-210rpm, and the length-to-diameter ratio is 39-41:
1.
8. The method for preparing a composite reinforced polyester fiber for bags according to claim 5, characterized in that... The mass ratio of polyethylene terephthalate chips, polyethylene glycol, tris(2,4-di-tert-butylphenyl) phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], modified nano zinc oxide, and tetrabutyl titanate is (88-92):(8-12):(0.1-0.3):(0.1-0.3):(3-5):(0.1-0.5).
9. The method for preparing a composite reinforced polyester fiber for bags according to claim 5, characterized in that... The conditions for melt spinning in step (3) are: spinneret orifice diameter of 0.24-0.26 mm, spinning speed of 2900-3100 m / min, and spinning temperature of 265-275℃.
10. The method for preparing a composite reinforced polyester fiber for bags according to claim 5, characterized in that... In step (5), the pH of the chitosan aqueous solution is adjusted to 4.5-5.5 with acetic acid.
Citation Information
Patent Citations
Multifunctional polyester fiber and preparation method thereof
CN112900076A
Modified polyester fiber and production method thereof
CN110344134A
Method for preparing fiber-grade zinc oxide antibacterial polyester master batch by melt on-line direct mixing process
CN117186449A
Method of preparing polyethylene glycol modified polyester filaments
US20010002737A1
Copolymerized polyester and polyester fiber formed from same
WO2014050652A1
Cited By
Nanocomposite antibacterial and mildew-proof polyester fiber and preparation method thereof
CN120719416B
Production method of strong yarn pulling rope
CN121700698A